2022
DOI: 10.1039/d2cp02766f
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-ion diffusion in the grain boundary of polycrystalline solid electrolyte Li6.75La3Zr1.5Ta0.5O12 (LLZTO): a computer simulation and theoretical study

Abstract: Lithium-ion diffusion ability in solid electrolytes is crucial for the performance and safety of lithium-ion batteries. However, the lithium-ion diffusion coefficient of Li6.75La3Zr1.5Ta0.5O12 (LLZTO) measured experimentally is much lower than...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Alternatively, the doping of Al at LLZO GBs was found to have a minimal impact on the Li-ion conductivity as a result of the immobile Al ions blocking nearby Li-ion hopping. DFT and AIMD simulations were also conducted for Ta-doped LLZO and it was again found that the GBs in this material result in significant interfacial resistance, possibly due to the formation of secondary phases with high Li-ion migration barriers …”
Section: Modeling Ion Transport At Grain Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the doping of Al at LLZO GBs was found to have a minimal impact on the Li-ion conductivity as a result of the immobile Al ions blocking nearby Li-ion hopping. DFT and AIMD simulations were also conducted for Ta-doped LLZO and it was again found that the GBs in this material result in significant interfacial resistance, possibly due to the formation of secondary phases with high Li-ion migration barriers …”
Section: Modeling Ion Transport At Grain Boundariesmentioning
confidence: 99%
“…DFT and AIMD simulations were also conducted for Ta-doped LLZO and it was again found that the GBs in this material result in significant interfacial resistance, possibly due to the formation of secondary phases with high Li-ion migration barriers. 74 Perovskite oxide solid electrolytes have also received attention due to their GB properties. We carried out an atomistic modeling study of GBs in Li 3x La (2/3)−x TiO 3 (0 < x < 0.16, LLTO) using classical MD simulations.…”
Section: Modeling Ion Transport At Grain Boundariesmentioning
confidence: 99%